In vivo evaluation of a biodegradable intraanastomotic membrane in a porcine model - Freund, Daniel C.; Wahl, Dennis; Grambow, Eberhard; Jaekel, Finn; Henne, Julia; Kantelberg, Richard; Kleemann, Hans; Prall, Friedrich; Zitzmann, Amelie R.; Vollmar, Brigitte; Hampe, Jochen; Leo, Karl; et al. (Frontiers in Surgery, 2026)
BackgroundAnastomotic leakage (AL) represents one of the most serious complications in gastrointestinal surgery, with reported incidence rates of up to 26%. Despite advancements in surgical techniques, early detection of AL remains challenging, and no reliable real-time monitoring system is currently available. In this study, we investigated a resorbable polydioxanone (PDO) membrane as a potential substrate for future sensor integration, aiming to facilitate real-time monitoring of anastomotic healing.MethodsIn eight German Landrace pigs, 34 ileal side-to-end stapler anastomoses were examined: GM1 (n = 7), GM2 (n = 10), and controls (n = 17). Membrane stability was monitored after implantation, while adhesion formation, burst pressure, and histology were assessed on postoperative day 7.ResultsBoth membrane geometries showed robust stability, with good anchorage of the large spokes within the anastomosis. Geometry 1 (GM1) exhibited higher burst pressure than Geometry 2 (GM2) (193 ± 43.6 vs. 155 ± 65.5 mmHg, p = 0.02). Compared with controls (167 ± 42.3 mmHg), neither GM1 (p = 0.053) nor GM2 (p = 0.379) differed significantly. Adhesions occurred in all groups, without significant differences. Histological evaluations showed typical granulation tissue and fibrosis, with granulocytic inflammation more common in GM1 without affecting anastomotic stability.ConclusionThis proof-of-concept study demonstrates that the PDO membrane can be safely incorporated into stapled anastomoses without compromising anastomotic healing. The membrane provides a stable, biocompatible platform suitable for future sensor integration, supporting the development of a diagnostic intraanastomotic device.